A Prospective, Longitudinal Study of the Effect of Remission on Cortical Thickness and Hippocampal Volume in Patients with Treatment-Resistant Depression. (22nd April 2015) - Phillips, Jennifer L.; Batten, Lisa A.; Tremblay, Philippe; Aldosary, Fahad; Blier, Pierre
Abstract : Background: Magnetic resonance imaging studies have provided evidence of structural modifications in cortical-limbic regions in major depressive disorder. To date, however, few studies have tracked structural changes in patients during treatment. This prospective, longitudinal imaging study investigated associations between brain structure and clinical responsiveness in a sample of patients with treatment-resistant major depressive disorder during an approximate 1-year follow-up period. Methods: FreeSurfer software was used to extract volume or cortical thickness values from 6 regions of interest (hippocampus, rostral middle frontal gyrus, orbitofrontal cortex, rostral and caudal anterior cingulate cortices, and inferior temporal gyrus) in patients (n = 26) and matched healthy controls (n = 28). Regions of interest were selected based on previous evidence of potential associations between morphometric characteristics in these regions and treatment response or remission. Analyses were conducted to compare volume and cortical thickness in patients and controls at baseline imaging, determine whether patients' brain structure at treatment initiation was associated with response over follow-up, and compare longitudinal changes in volume and cortical thickness in patients who achieved sustained 6-month remission (Montgomery-Åsberg Depression Rating Scale Score ≤12) with nonremitters. Results: Patients and controls showed no structural differences at baseline. Among patients, thicker right caudal anterior cingulate cortex at baseline was associated with greater symptom improvement over follow-up. Remitters and nonremitters showed subtle changes in volume and thickness over time in opposing directions, with increased hippocampal volume and cortical thickness in the rostral middle frontal gyrus, orbitofrontal cortex, and inferior temporal gyrus in remitters, and decreased volume or thickness in these regions in nonremitters. Conclusions: The results suggest that longitudinal structural trajectories may differ in major depressive disorder patients according to their clinical response to treatment.